Effect of Soaking Cereals with Ethylene Glycol in Tolerance And some of its qualities - Nahla Hmook; Mohammed Sadek (College of Education for Pure Sciences, 2019)
The study was carried out during the winter of 2002-2003 ,using spring wheat Triticum aestivum L.(Abu-Greab-3-cultivar).The study aimed to investigate the possibility of using ethylen glycol (an antifreezing solution )for induction of freezing tolerance in wheat plants by seeds soaking method. The study was carried out in three replicates and designated as (4×5)factorial experiment according to randomize complete block design with two factors. The first factor was ethylen glycol concentrations with comprised four levels (0,5,10,and 20%,v/v)while the second factor comprised five periods of exposure to -5 c(0,12,24,48 and 72 hrs). Different concentrations of ethylen glycol were showed significant effects at 0.05 level of significant in:-area of the first leaf after 15,30 and 60 days ,area of second leaf after 30 and 60 days;area of third leaf after 60 days ;fresh weight of first ,second and third leaves ; dry weight of second and third leaves; plant dry weight ;No. of leaves in main stem after 30 days ; total No. of leaves /plant after 60 days and the No.of stomata/mm2 , while there were no significant effects in amount of protein and chlorophyll a and b. Different exposure periods were showed significant effects in :- area of first and second leaves after 15,30 and 60days; area of third leaf after 30 and 60 days; fresh and dry weight of first ,second and third leaves and the complete plant ;No.of leaves in main stem after 15 and 30 days ;Total No. of leaves / plant after 60 days and chlorophyll a and b ,while no significant effects were noticed in :No. of stomata/mm2 of leaf surface and amount of protein.All the interactions between the two factors were significant except for protein amount. Analysis of regression between ethylene glycol concenterations and exposure periods with all studied parameters were also done for those showed significant differences.